Predicting Attitudes Toward Marital Infidelity in Couples Based on Attachment Styles and Personality Traits with the Mediation of Coping Strategies (Gender Comparison) - Khezrlou, Elnaz; Aghayousefi, Alireza; Ebrahim Moghadam, Hossein (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The present study aimed to predict attitudes toward marital infidelity in couples based on attachment styles and personality traits with the mediation of coping strategies (gender comparison).Methods: The research method was correlational and used structural equation modeling. The statistical population included all married women and men aged 25 to 45 in Tehran. A sample of 420 individuals, comprising 210 women and 210 men, was selected through convenience sampling. Research data were collected using the Whately Marital Infidelity Attitude Questionnaire (2006), the Collins and Read Attachment Styles Questionnaire (1994), the Cattell 16 Personality Factor Test (1973), and the Lazarus-Folkman Coping Strategies Questionnaire (1988). Relationships between variables were assessed using Pearson's correlation test, and the research model was evaluated using the Partial Least Squares (PLS) structural equation modeling technique. The mediation role was also assessed using the bootstrapping method in Smart PLS software. Data analysis was performed using SPSS version 27 and Smart PLS version 3.Findings: The research findings indicated that in the female sample, risk-taking as a personality trait could predict marital infidelity (p < .05). In the male sample, the conscientiousness personality trait directly predicted marital infidelity, while insecure attachment predicted marital infidelity both directly and indirectly through the avoidant-escape coping style (p < .05).Conclusion: The results showed that insecure attachment influences the tendency toward marital infidelity in the male group. Additionally, the conscientiousness factor influences the tendency toward marital infidelity in the male group, and the avoidance and escape strategies influence the tendency toward marital infidelity in the male group. The results also demonstrated that secure attachment negatively impacts the problem-solving coping strategy in the female group. Secure attachment negatively impacts the avoidant-escape strategy in the female group but positively impacts it in the male group. Insecure attachment positively impacts the avoidant-escape strategy in both the female and male groups. The conscientiousness factor positively impacts the problem-solving coping strategy in the female group. Moreover, sociability positively impacts the avoidant-escape strategy in the male group, while emotional stability negatively impacts the avoidant-escape strategy in the overall and male groups. Risk-taking negatively impacts the avoidant-escape strategy in the overall and male groups. These results showed no relationship between insecure attachment and the tendency toward marital infidelity in women.